2005
DOI: 10.1159/000085368
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Chronic Obstructive Pulmonary Disease and Rhinitis in Northern Greece

Abstract: Background: Chronic obstructive pulmonary disease (COPD) constitutes one of the main factors responsible for morbidity and mortality worldwide. Rhinitis has a high prevalence, but its relationship to COPD has not been determined. Objectives: To estimate the prevalence of COPD and rhinitis in northern Greece and to examine their correlation. Patients andMethods: Of a total of 8,151 subjects (aged 21–80 years, from three regions of northern Greece) invited to participate in the study, 6,112 (75%) were included. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
1
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 32 publications
6
25
1
4
Order By: Relevance
“…In the pre-crisis period 73.3% of COPD patients in Greece were reported to be males [31], while the sex-standardised COPD prevalence was 11.6% for men and 4.8% for women [31]. Analogous results were obtained from a study conducted in northern Greece, in which the prevalence of COPD in males was shown to be 8.2% and in females was 2.5% [32]. Likewise during the crisis, MITSIKI et al [35] estimated that the male to female ratio in Greece was 2.5:1 and another study conducted in 2010 in Thessaly (central Greece) in 2010 found that women represented 12.5% of COPD patients [33].…”
Section: Profile Of Copd Patients In Greece During the Crisissupporting
confidence: 59%
See 3 more Smart Citations
“…In the pre-crisis period 73.3% of COPD patients in Greece were reported to be males [31], while the sex-standardised COPD prevalence was 11.6% for men and 4.8% for women [31]. Analogous results were obtained from a study conducted in northern Greece, in which the prevalence of COPD in males was shown to be 8.2% and in females was 2.5% [32]. Likewise during the crisis, MITSIKI et al [35] estimated that the male to female ratio in Greece was 2.5:1 and another study conducted in 2010 in Thessaly (central Greece) in 2010 found that women represented 12.5% of COPD patients [33].…”
Section: Profile Of Copd Patients In Greece During the Crisissupporting
confidence: 59%
“…A number of studies have shown that COPD has been more prevalent among smokers, older adults and males in Greece [31][32][33]35]. COPD patients have displayed this profile both pre-crisis and throughout the crisis period.…”
Section: Profile Of Copd Patients In Greece During the Crisismentioning
confidence: 99%
See 2 more Smart Citations
“…A study from Greece compared the prevalence of rhinitis in subjects with and without COPD. 12 COPD was confirmed with spirometry, and rhinitis was defined by the presence of nasal symptoms together with objective evidence of reduced nasal airflow at rhinomanometry. Of the 6112 subjects assessed, 6% had COPD and 25% had rhinitis.…”
Section: Nasal Symptoms In Copdmentioning
confidence: 99%